2009
DOI: 10.1152/ajprenal.00110.2009
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of JAK-STAT signaling/function after cyclophosphamide-induced bladder inflammation in female rats

Abstract: The role of JAK-STAT signaling in urinary bladder inflammation and referred somatic sensitivity has not been addressed. The contribution of JAK-STAT signaling pathways in CYP-induced bladder hyperreflexia and referred somatic hypersensitivity was determined in CYPtreated rats using a JAK2 inhibitor, AG490. Acute (4 h; 150 mg/kg ip), intermediate (48 h; 150 mg/kg ip), or chronic (75 mg/kg ip, once every 3 days for 10 days) cystitis was induced in adult, female Wistar rats with CYP treatment. Phosphorylation sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
51
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(62 citation statements)
references
References 55 publications
11
51
0
Order By: Relevance
“…Additionally, in the mechanical hyperalgesia test, AG490 treatment increased the PWT at all doses tested; however, this effect was not statistically significant. Therefore, we speculate that AG490 is more effective at reducing mechanical allodynia as measured in previous studies (5,6), than for reducing mechanical hyperalgesia, as shown in the present study. It is also possible that differences in animal model, and route and dose of AG490 administration influence the effects of AG490 on the response to mechanical stimuli.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Additionally, in the mechanical hyperalgesia test, AG490 treatment increased the PWT at all doses tested; however, this effect was not statistically significant. Therefore, we speculate that AG490 is more effective at reducing mechanical allodynia as measured in previous studies (5,6), than for reducing mechanical hyperalgesia, as shown in the present study. It is also possible that differences in animal model, and route and dose of AG490 administration influence the effects of AG490 on the response to mechanical stimuli.…”
Section: Discussionsupporting
confidence: 71%
“…in a volume of 100 µl. As reported earlier, the in vivo pharmacological effects of AG490 were observed 4 h after treatment (5,6). Thus, the behavioral tests were performed before (baseline assessment) and 4 h after treatment.…”
Section: Experimental Groups Design and Treatmentmentioning
confidence: 92%
See 1 more Smart Citation
“…On day 8, 24 h after presentation of the last stressor, a lower midline abdominal incision was made under general anesthesia with 2-3% isoflurane using aseptic techniques (16,33,40,68). One end of polyethylene tubing (PE-50; Clay Adams, Parsippany, NJ) was flared with a flame and inserted in the dome of the bladder and secured in place with a 6-0 nylon purse-string suture (16,33,40,68).…”
Section: Intravesical Catheter Implantmentioning
confidence: 99%
“…One end of polyethylene tubing (PE-50; Clay Adams, Parsippany, NJ) was flared with a flame and inserted in the dome of the bladder and secured in place with a 6-0 nylon purse-string suture (16,33,40,68). The distal end of the tubing was tunneled subcutaneously to the back of the neck where it was buried in an incision in the back of the neck, out of the animal's reach (16,33,40,68). Rats received buprenorphine (0.05 mg/kg sc) starting at the time of surgery and then every 8 -12 h postoperatively for a total of four doses.…”
Section: Intravesical Catheter Implantmentioning
confidence: 99%